Respuesta :

[tex]\qquad\qquad\huge\underline{{\sf Answer}}[/tex]

Let's solve ~

[tex]\qquad \tt \dashrightarrow \:10 {x}^{2} - 25x + 15 = 0[/tex]

[tex]\qquad \tt \dashrightarrow \:5(2x {}^{2} - 5x + 3) = 0[/tex]

[tex]\qquad \tt \dashrightarrow \:2x {}^{2} - 5x + 3 = 0[/tex]

[tex]\qquad \tt \dashrightarrow \:2x {}^{2} - 3x - 2x + 3 = 0[/tex]

[tex]\qquad \tt \dashrightarrow \:x(2x - 3) - 1(2x - 3) = 0[/tex]

[tex]\qquad \tt \dashrightarrow \:(x - 1)(2x - 3) = 0[/tex]

Therefore, the required factors are ~ (x - 1) and (2x - 3)

So, correct choice is B